1983
DOI: 10.1159/000272877
|View full text |Cite
|
Sign up to set email alerts
|

A Process Model of the Pregnancy Course

Abstract: A phase model describing the course of the woman’s first pregnancy is proposed. In complementing the dominant treatments of pregnancy within medical and clinical domains, a more extended view of pregnancy as both a biological and psycho-social process is outlined. The pregnancy course is considered an integral segment within the woman’s full life course – both dependent upon and influencing other segments. In the present model, four ideal phase types are distinguished: a disruption phase of radical change, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…They must also modify their understandings of themselves and who they are in relationship to other people (Steinberg, 2005). Gloger-Tippelt (1983) argued that this process begins during the prenatal months, given that pregnancy is often a catalyst for self-evaluation and self-reconstruction among first-time mothers (Smith, 1994). The practice of mothering furthers identity changes, particularly because women are faced by the realities of motherhood in juxtaposition with their ideals of motherhood.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…They must also modify their understandings of themselves and who they are in relationship to other people (Steinberg, 2005). Gloger-Tippelt (1983) argued that this process begins during the prenatal months, given that pregnancy is often a catalyst for self-evaluation and self-reconstruction among first-time mothers (Smith, 1994). The practice of mothering furthers identity changes, particularly because women are faced by the realities of motherhood in juxtaposition with their ideals of motherhood.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…At that time the construction of scales to measure and quantify the mother-foetus relationship (MFR), for example, the Prenatal Tool (Rees, 1980) and the Maternal Foetal Attachment Scale (MFAS; Cranley, 1981) had given rise to empirical research testing seminal theories. These theories supposed that during pregnancy the development of a relationship with the unborn child is a key developmental task in the successful psychological adjustment for all pregnant women (Gloger-Tippelt, 1983;RaphaelLeff, 1991;Stern, 1995;Valentine, 1982). For primigravidas the formation of a maternal identity, based on representations of the self as mother, was thought to be another important developmental task (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A number of writers have suggested that pregnancy is a time for introspection (e.g. Gloger-Tippelt, 1983;Shereshefsky, Plotsky, & Lockman, 1973) and, as Brindle et al (1991) have suggested, this would not be surprising given that, particularly for rst-time mothers, this is an important transition period in their lives (Pines, 1972;Zajicek, 1981). Personal accounts of becoming a mother (e.g.…”
mentioning
confidence: 99%